Kelantan United Football Club / Azraei Hafiy Jeffry Efendy - Jeffry Efendy, Azraei Hafiy (2022)
Kelantan United Football Club previously known as MPKB-BRI FC enter the Malaysian football competition in 2016 when the club was accepted to compete in 2016, Malaysia FAM League starting from 2019 season the club has been rebranded to Kelantan United as an effort to bring in local area support. For this project, i would say this is about to be a major rebrand for Kelantan United football club because i applied new and modern design to make this football club has it own strong identity. Besides that this would be a reason to gain more fans and supporters around Malaysia.